2004
DOI: 10.1590/s0004-27492004000200011
|View full text |Cite
|
Sign up to set email alerts
|

Aderência bacteriana in vitro a lentes intra-oculares de polimetilmetacrilato e de silicone

Abstract: Objetivos: Verificar a aderência bacteriana a lentes intra-oculares de silicone e de polimetilmetacrilato como possível fator de risco no desenvolvimento de endoftalmite pós-operatória, utilizando-se um modelo in vitro com três microrganismos potencialmente patogênicos. Métodos: As análises foram realizadas com cepas de Staphylococcus aureus ATCC 29213, Staphylococcus epidermidis (amostra clínica) e Pseudomonas aeruginosa ATCC 27853 incluindo a determinação de curvas de crescimento, testes para verificação de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…Hydrophobic materials are reported as surfaces that provide a greater bacterial adherence (6,15). The greater hydrophobicity of polyethylene compared to stainless steel can be an explanation to the higher counts of adhered Salmonella cells on polyethylene as observed in our results.…”
Section: Resistance Of Adhered Cells To Sanitizerssupporting
confidence: 66%
“…Hydrophobic materials are reported as surfaces that provide a greater bacterial adherence (6,15). The greater hydrophobicity of polyethylene compared to stainless steel can be an explanation to the higher counts of adhered Salmonella cells on polyethylene as observed in our results.…”
Section: Resistance Of Adhered Cells To Sanitizerssupporting
confidence: 66%
“…). Researchers have shown that bacterial adherence decreases with decreasing contact angle and increasing surface tension of synthetic materials .…”
Section: Resultsmentioning
confidence: 99%
“…Thereafter, dilution series were prepared with each solution after sonication (10 -2 to 10 -5 ), and they were inoculated on TSA plates and incubated at 37ºC for 24 h in order to verify the colony's growth that had not adhered to the slides. The dilution that offered best counting conditions was used to achieve the experimental protocols (Locatelli et al, 2004;Ferreira et al, 2009;Silva, 2010). Before the sonication and washing steps, the slides analyses by SEM were not performed because at this moment the test specimen remained full of proteins, carbohydrates and other compounds from the culture medium (visible to the naked eyes) which compromised the visualization of the colonies of P. aeruginosa by SEM.…”
Section: Bacterial Growth Evaluation After Sonicationmentioning
confidence: 99%
“…Finally, the slides were metalized in Balzers Union FL -9496 (Balzers, Germany) with 2 nm of gold for two minutes, and subsequently analyzed in the scanning electron microscope JSM 5310 (Jeol, Japan) at high vacuum in secondary electron mode (Locatelli et al, 2004;Ferreira et al, 2009;Silva, 2010).…”
Section: Slides Evaluation By Scanning Electron Microscopy (Sem)mentioning
confidence: 99%
See 1 more Smart Citation